Procalcitonin Monitoring as a Guide for Antimicrobial Therapy: A Review of Current Literature. Issue 5 (23rd April 2018) - Covington, Elizabeth W.; Roberts, Megan Z.; Dong, Jenny
Abstract : Effective antimicrobial stewardship practices are increasingly essential to best utilize the current arsenal of antimicrobials for the shortest necessary duration to minimize the development of antimicrobial resistance, secondary infections, and health care costs. Monitoring of serum procalcitonin (PCT) levels represents an effective antimicrobial stewardship strategy to differentiate bacterial infections from viral infections and noninfectious inflammatory conditions. Current literature illustrates the merits of PCT monitoring in reducing duration of antibiotic therapy without detrimental effects on mortality or infection relapses. However, the interpretation of PCT levels can be challenging, especially in light of comorbid disease states that can elevate PCT levels. This review sheds light on the utility of PCT monitoring, as well as providing insight into the practical interpretation of PCT levels. Much of the current literature surrounding PCT monitoring consists of use among patients with lower respiratory tract infections or in the critically ill. Overall, studies have demonstrated shorter antibiotic therapy durations when PCT monitoring is utilized. No studies to date have found increased rates of mortality or infection relapses, suggesting that PCT monitoring is not only effective, but also safe when used as a guide for antimicrobial therapy. Nonetheless, many conditions were shown to elevate PCT serum concentrations, even in the absence of bacterial infections, which can make interpretation of PCT concentrations challenging. Two common conditions that affect the accurate interpretation of PCT levels are renal dysfunction and congestive heart failure. Limited studies have been performed in these populations, but current available data propose the need for higher PCT thresholds in those with renal dysfunction or congestive heart failure and support utilizing PCT trends to monitor clinical improvement from bacterial infections. Evidence also suggests that PCT monitoring is cost‐effective, as long as the test is ordered judiciously. In summary, PCT monitoring represents a promising antimicrobial stewardship strategy to limit exposure to unnecessary antimicrobial therapy.